A new Lepeophtheirus (Copepoda: Siphonostomatoida: Caligidae) from Isla del Coco National Park, Costa Rica, Eastern Tropical Pacific - Suárez-Morales, Eduardo; Gasca, Rebeca (Revista de Biología Tropical, 2012)
Among the several groups of copepods that are teleost parasites, the siphonostomatoid family Caligidae is by far the most widespread and diverse. With more than 108 nominal species, the caligid genus Lepeophtheirus von Nordmann is one of the most speciose. There are no reports of this genus in Costa Rican waters. A new species of Lepeophtheirus is herein described based on female specimens collected from plankton samples in waters off Bahía Wafer, isla del Coco, an oceanic island in the Eastern Tropical Pacific. The new species, L. alvaroi sp. nov., has some affinities with other congeners bearing a relatively short abdomen, a wider than long genital complex and a 3-segmented exopod of leg 4. it differs from most of these species by the presence of an unbranched maxillular process and by the relative lengths of the terminal claws of leg 4, with two equally long elements. it is most closely related to two other Eastern Pacific species: L. dissimulatus Wilson, 1905 and L. clarionensis Shiino, 1959. it differs from these species by the proportions and shape of the genital complex, the shape of the sternal furca, the relative length of the maxillar segments, the absence of a pectiniform process on the distal maxillar segment, the length of leg 4 and the armature of leg 5. The new species represents the first Lepeophtheirus described from Costa Rican waters of the Pacific. The low diversity of this genus in this tropical region is explained by its tendency to prefer hosts from temperate latitudes. Until further evidence is found, the host of this Lepeophtheirus species remains unknown. Citation: Suárez-Morales, E. & R. Gasca. 2012. A new Lepeophtheirus (Copepoda: Siphonostomatoida: Caligidae) from isla del Coco National Park, Costa Rica, Eastern Tropical Pacific. Rev. Biol. Trop. 60 (Suppl. 3): 235-242. Epub 2012 Dec 01.